2006
DOI: 10.1111/j.1525-1497.2006.00614.x
|View full text |Cite
|
Sign up to set email alerts
|

Nonbacterial Thrombotic Endocarditis with Recurrent Embolic Events as Manifestation of Ovarian Neoplasm

Abstract: We describe the case of a 43-year-old woman with transient ischemic neurologic deficits and recurrent systemic and pulmonary emboli in whom infectious work-up and extensive thrombophilic evaluation were unremarkable. Transesophageal echocardiography (TEE) established the diagnosis of nonbacterial thrombotic endocarditis (NBTE). This is a rare condition often associated with hypercoagulable states or advanced malignancy such as adenocarcinomas, characterized by cardiac vegetations along valvular coaptation line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 18 publications
(68 reference statements)
0
48
1
Order By: Relevance
“…Most of the symptoms of NBTE are related to embolic events, primarily cerebral embolism, often leading to cortical symptoms, such as unilateral paralysis, aphasia and agnosia (4,12). Other sites prone to emboli originating from NBTE include the coronary arteries, spleen and kidneys (13). However, it is extremely rare that NBTE causes cardiac valve lesions and acute heart failure, as in the present case.…”
Section: Low Power Fieldmentioning
confidence: 53%
“…Most of the symptoms of NBTE are related to embolic events, primarily cerebral embolism, often leading to cortical symptoms, such as unilateral paralysis, aphasia and agnosia (4,12). Other sites prone to emboli originating from NBTE include the coronary arteries, spleen and kidneys (13). However, it is extremely rare that NBTE causes cardiac valve lesions and acute heart failure, as in the present case.…”
Section: Low Power Fieldmentioning
confidence: 53%
“…There are other mechanisms that link cancer to stroke and these have been documented in other case reports of ovarian cancer presenting as cerebral infarction 17 18. They include non-bacterial thrombotic endocarditis, where sterile vegetations grow on the aortic and/or mitral valve, and are thought to be composed of disrupted fibrin and platelets, and are susceptible to embolisation 17.…”
Section: Discussionmentioning
confidence: 98%
“…A study of cerebral infarction associated with ovarian cancer has identified the main cause as NBTE or hypercoagulability [9]. The hypercoagulable state in patients with ovarian cancer cannot be influenced by standard anticoagulation therapy with heparin or coumadin derivatives, but it has been reported to be stopped by curative resection of the tumor, avoiding an extremely poor outcome [10,11]. Treatment of the hypercoagulable state itself does not have a great influence on prognosis; successful treatment of the primary disease is said to most influence the prognosis.…”
Section: Discussionmentioning
confidence: 99%